Clerk, Chancellor, Castaway (1374–1419) - Tiago Viúla de Faria (Medievalista)
A former member of the parish clergy and an occasional servant of Richard II, the scholar Adam Davenport became one of the main household officials of the Portuguese queen, Philippa of Lancaster, the daughter of John of Gaunt and the sister of Richard II’s usurper, Henry IV. On stepping down from office and Portugal’s royal court, he returned to his native country only to meet with Henry IV’s continued disapproval, which eventually led him to a terminus vitae in relative modesty and obscurity.This paper traces Adam Davenport’s professional trajectory of 45 years, from 1374 to 1419, across contrastive political regimes in two different countries, first as a local cleric, then as a senior administrator, and eventually as an unwaged outsider. As the social and financial ties between Davenport and his consecutive benefactors were kept or lost, according to the distribution of grace and the varying configuration of affinities, so Davenport’s fortune changed. The details of this three-tiered career put into focus the critical role played by displacement (geographical as much as societal) and the secular patronage on which men like Davenport — a middling member of an expanding clerical class — came to depend for survival.